Prototipe Aplikasi Mobile SmartKuliner untuk Promosi dan Edukasi Produk UMKM Kuliner Kreatif dengan Pendekatan Cross-Platform - Pramono Pramono; Nibras Faiq Muhammad (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
The culinary creative sector within Micro, Small, and Medium Enterprises (MSMEs) plays a vital role in supporting the local economy, yet its development is constrained by limited digital marketing and insufficient product education. This research introduces SmartKuliner, a cross-platform mobile application prototype intended to strengthen digital promotion and consumer learning for culinary MSMEs. Developed using the Research and Development (R&D) method with a prototyping approach, the application features interactive multimedia such as product catalogs, educational materials, and branding support. Usability evaluation through the System Usability Scale (SUS) confirmed its practicality and ease of use. The results show that SmartKuliner provides MSMEs with an accessible tool to expand market opportunities and enhance product knowledge.